2020
DOI: 10.3390/medicina56040192
|View full text |Cite
|
Sign up to set email alerts
|

The Role of VEGFA, COX2, HUR and CUGBP2 in Predicting the Response to Neoadjuvant Therapy in Rectal Cancer Patients

Abstract: Background and objectives: The effectiveness of neoadjuvant therapy, which is commonly used for stage II-III rectal cancer (RC) treatment, is limited. Genes associated with the pathogenesis of RC could determine response to this treatment. Therefore, the aim of this study was to investigate the potential predictive value of VEGFA, COX2, HUR and CUGBP2 genes and the associations between post-treatment changes in gene expression and the efficacy of neoadjuvant therapy. Materials and Methods: Biopsies from RC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…This trend was remarked in COX-2 mRNA levels also (68% and 36.2% decrease at 24 h and 48 h, respectively). Lesser reduction of 5FU induced COX-2 and VEGF mRNA at 48h could be due to increased stabilization by HuR protein which is required for their mRNA stability, therefore, helps sustain their expression for a longer period [48]. The other reason is the low half-life of SR033, as reflected in our preliminary stability experiments (not shown), where the activity (EC50 value) of SR033 decreases by 48 h. To address the half-life issue of SR033, we exposed MCF-7 to 5FU for 48 h and SR033 for last 24 h and observed that SR033 decreases VEGF and COX-2 gene expression levels significantly as compared to their respective controls.…”
Section: Discussionmentioning
confidence: 99%
“…This trend was remarked in COX-2 mRNA levels also (68% and 36.2% decrease at 24 h and 48 h, respectively). Lesser reduction of 5FU induced COX-2 and VEGF mRNA at 48h could be due to increased stabilization by HuR protein which is required for their mRNA stability, therefore, helps sustain their expression for a longer period [48]. The other reason is the low half-life of SR033, as reflected in our preliminary stability experiments (not shown), where the activity (EC50 value) of SR033 decreases by 48 h. To address the half-life issue of SR033, we exposed MCF-7 to 5FU for 48 h and SR033 for last 24 h and observed that SR033 decreases VEGF and COX-2 gene expression levels significantly as compared to their respective controls.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support a predictive potential role also for COX2 that appears to be associated with a higher chance of pathological complete response when expressed above the herein defined cutoff value. Despite the well-accepted role of COX2 in supporting tumor growth and development 28 , literature data are conflicting regarding its predictive significance in locally advanced rectal cancer, with some studies sustaining 29–31 and others disproving 32,33 a COX2 involvement in predicting the neoadjuvant chemoradiotherapy efficacy. These discrepancies might be partially attributable to the heterogeneities of study cohorts and/or therapeutic schemes as well as to the huge methodological heterogeneity in the scoring system used to classify COX2 expression.…”
Section: Discussionmentioning
confidence: 99%